Pro-Tumoral Functions of Autophagy Receptors in the Modulation of Cancer Progression - Cerda-Troncoso, Cristóbal; Varas-Godoy, Manuel; Burgos, Patricia V. (Frontiers in Oncology, 2021)
Cancer progression involves a variety of pro-tumorigenic biological processes including cell proliferation, migration, invasion and survival. A cellular pathway implicated in these pro-tumorigenic processes is autophagy, a catabolic route used for recycling of cytoplasmic components to generate macromolecular building blocks and energy, under stress conditions, to remove damaged cellular constituents to adapt to changing nutrient conditions and to maintain cellular homeostasis. During autophagy, cells form a double-membrane sequestering a compartment termed the phagophore, which matures into an autophagosome. Following fusion with the lysosome, the cargo is degraded inside the autolysosomes and the resulting macromolecules released back into the cytosol for reuse. Cancer cells use this recycling system during cancer progression, however the key autophagy players involved in this disease is unclear. Accumulative evidences show that autophagy receptors, crucial players for selective autophagy, are overexpressed during cancer progression, yet the mechanisms whereby pro-tumorigenic biological processes are modulated by these receptors remains unknown. In this review, we summarized the most important findings related with the pro-tumorigenic role of autophagy receptors p62/SQSTM1, NBR1, NDP52 and OPTN in cancer progression. In addition, we showed the most relevant cargos degraded by these receptors that have been shown to function as critical regulators of pro-tumorigenic processes. Finally, we discussed the role of autophagy receptors in the context of the cellular pathways implicated in this disease, such as growth factors signaling, oxidative stress response and apoptosis. In summary, we highlight that autophagy receptors should be considered important players of cancer progression, which could offer a niche for the development of novel diagnosis and cancer treatment strategies.